Care Foundation Electronic Medical Record System Cryptographic-Based Approach and Role-Based Access Control - Khoo, Xiao Hui; Ramli, Sofia Najwa Binti (Applied Information Technology And Computer Science, 2023)
An electronic medical record (EMR) system is software that allows electronic entry, storage, and maintenance of digital medical data. EMR systems have been a great asset to the healthcare community. However, a significant number of privacy issues are raised by a shift from paper-based systems to integrated and electronic ones. Data breaches in the healthcare industry are increasing rapidly, and the general adoption rate of EMR is comparatively low due to security and privacy issues. Therefore, this project intends to develop a secure EMR system that integrates cryptography and role-based access control into the implementation of the system based on the Object-Oriented Software Development (OOSD) methodology using Jakarta Servlet. The user acceptance testing result shows that the EMR system is generally well-accepted by the end-users. Overall, all the objectives have been achieved. Future work may consider expanding the scope of development in terms of platform and functions.